Rethinking copyright for sustainable human development : higher education and access to knowledge - Hirko, Sileshi Bedasie (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book explores the interface between copyright and higher education, and their complementarities for the advancement of sustainable human development. Constituted of human capabilities prerequisite for valuable beings and doings, human development is noted as freedoms essential for human flourishing"--
Includes bibliographical references and index.
Keywords: Education, Higher; Copyright; Academic freedom; Developmental psychology; Sustainable development